Republic of Kazakhstan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper conducts a review of taxes on labor in Kazakhstan, which, despite the current relatively low level of collections, have the potential to become an important source of non-oil fiscal revenue. This paper focuses on one group of non-oil taxes, personal income tax and other taxes on labor, and reviews their effective burden, progressivity, and efficiency. These taxes are found to have limited responsiveness to oil-sector fluctuations, and thus help enhance the resilience of public finance to oil shocks. The existing labor tax system is characterized by a low, flat headline rate, limited progressivity except at the lower end of household income distribution due to deduction of the minimum wage, and a relatively high tax burden mainly born by the formal sector. Having a more equitable and efficient labor tax system would involve a targeted strategy for deductions and exemptions, expanding the tax base, and continuing to improve tax design, administration, and collection enforcement.